Analysis of the Use of LabXChange as a Virtual Laboratory Media to Improve Digital and Information Literacy for Biology Education Undergraduate Students - Milla Listiawati; Sri Hartati; Rena Denya Agustina; Riki Purnama Putra; Shidiq Andhika (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
Learning media is very important in order to facilitate learning or the income of information. In this 21st century, learning is not only focused on how to get but also how to find. 21st-century learning is also emphasized on digital literacy and also information literacy which is considered a fast door to learning. High digital literacy and information literacy, will facilitate the learning process carried out by students. This study aims to determine whether using LabXChange can improve or facilitate subjects in digital literacy and information literacy. The pre-Experimental design was used as a method in this study with a one-group pretest-posttest design. The research subjects were 15 subjects with a sampling technique purposive sampling. This study obtained the results with H0 = Ha ≠ Hb = Hc, which means, the 15 subjects can increase digital and information literacy  with the use of LabXChange as a media for students